MARKETING SUPPORT FOR ANTI-CRISIS MANAGEMENT OF AN AGRICULTURAL ENTERPRISE - Mariia Bahorka; Liudmila Kvasova; Yuliia Yakubenko (Izdevnieciba "Baltija Publishing", 2023)
The purpose of the article is to study the theoretical approaches of anti-crisis management, to generalise the causes of crisis phenomena of agricultural enterprises, to determine the main components of marketing support in the anti-crisis management system to optimise the "producer-market-consumer" chain in order to avoid and overcome the crisis state of the enterprise. The methodological basis of the study was a synthesis of the results of applied research in economics, scientific works of domestic and foreign scientists, which highlighted the basic theories of competitive advantage, competitiveness and marketing management. Results. The article examines theoretical approaches to crisis management, summarises the causes of crisis phenomena in agricultural enterprises, defines the main components of marketing support in the crisis management system to avoid the vulnerability of the enterprise to crisis phenomena and eliminate their consequences. Practical results. The marketing support of an agricultural enterprise in the anti-crisis management system is necessary because without it the enterprise will not be able to function normally and use its resources productively and profitably. Value/originality. It has been established that the purpose of marketing in anti-crisis management is to ensure the process of production and sale of the most demanded goods on the market, which will bring the greatest benefit to the enterprise and ensure profitable activity. It has been proved that the concept of pre-marketing includes the use of special tools even in the condition of stable development and functioning of the enterprise.